Effects of hemicellulose on intestinal mucosal barrier integrity, gut microbiota, and metabolomics in a mouse model of type 2 diabetes mellitus - Liu, Huan; Xu, Jihao; Yeung, Chiuwing; Chen, Qikui; Li, Jieyao (Frontiers in Microbiology, 2023)
Abstract BACKGROUND & AIMS: Impaired gut barrier contributed to the progression of type 2 diabetes mellitus (T2DM) and gut microbiota and metabolome played an important role in it. Hemicellulose, a potential prebiotics, how its supplementation impacted the glucose level, the impaired gut barrier, and the gut microbiota and metabolome in T2DM remained unclear. METHODS: Mice were arranged randomly into 4 groups: db/db mice fed by compositionally defined diet (CDD), db/db mice fed by CDD with 10% and 20% hemicellulose supplementation, and control mice fed by CDD. Body weight and fasting blood glucose levels were monitored weekly. The gut barrier was evaluated. Fresh stool samples were analyzed by metagenomic sequencing and liquid chromatography-mass spectrometry to detect the changes of the gut microbiota and metabolome. Systemic and colonic inflammation were evaluated. Results: Better glycemic control, restoration of the impaired gut barrier, and lowered systemic inflammation levels were observed in db/db mice with supplementation of 10% or 20% hemicellulose . The gut microbiota showed significant differences in beta diversity among the 4 groups. 15 genera with differential relative abundances and 59 significantly different metabolites were found. The redundant Faecalibaculum and Enterorhabdus in the db/db group were abrogated by the hemicellulose. The increased succinate and ursodeoxycholic acid (UDCA) after hemicellulose treatment were negatively corelated with Bifidobacterium, Erysipelatoclostridium, and Faecalibaculum. In addition, hemicellulose decreased the colonic expressions of TLR2/4 and TNF-α in db/db mice. Conclusion: Hemicellulose might be a potential treatment for T2DM by restoring the impaired intestinal mucosal barrier and modifying gut microbiota and metabolome.